Influence of blanking distance of materials on increase in blanking vibration using screw drive servo press - Tomohiro MURAKAMI (The Japan Society of Mechanical Engineers, 2016)
In this study, we propose a suitable blanking velocity for the blanking of different materials using a screw drive servo press. Under this blanking velocity, press blanking can be carried out without causing an increase in blanking vibration. Blanking noise and vibration are causes of pollution. Moreover, blanking vibration reduces the precision of press work products and the lifetimes of the press machine and press die. Recently, a servo press has been developed for advanced press work. A screw drive servo press does not have a mechanical bottom dead center but location of its slide is constantly measured, and highly precise location and speed control are achieved by a feedback control system. However, blanking vibration is increased at high blanking velocities using this machine. Our previous study clarified that the blanking velocity and blanking time affect of blanking vibration. However, the influence of the material is not clear. Thus, we studied the relationship between the material and the vibration in blanking with a screw drive servo press both experimentally, and by simulation. At the experiment, we compared the blanking vibration of four materials with different tensile strengths. As a result, we found that the blanking time is different for each material, because the blanking distance depends on each material. And finally, we propose an equation as a general formula which calculates the threshold of blanking velocity vt to prevent an increase in blanking vibration.